PENERAPAN ASAS CEPAT DALAM PERKARA PERBUATAN MELANGGAR HUKUM DI PENGADILAN NEGERI TANGERANG (Contoh Kasus: Putusan Nomor 498/Pdt.G/2016/PN Tng) - Ezra De Artah Sasta; Ning Adiasih (Fakultas Hukum Universitas Tarumanagara, 2018)
The purpose of this study is to know how the case process in the Tangerang District Court, how its application with the Supreme Court Circular No. 2 of 2014 in the acceleration of Civil procedure law cases in the Tangerang District Court from 2015 to 2017. By using normative juridical research methods, concluded: 1. The case process that occurred in the State Court as from the beginning until the judge's decision became the most effective alternative today. Because it can be seen from cases that have been systematic for the realization of justice. 2. The establishment of the Supreme Court Circular No. 2 of 2014 is very useful and provides basic guidance in the Tangerang District Court in the event of a speedy trial. However, in the practice of the Tangerang District Court on the issue of implementation in accordance with the Supreme Court Circular No. 2 of 2014 in the court environment does not go according to the hope of the formation of the regulation. There are some disputes that have passed the right time, although basically to deal with civil cases with the rules will not be long. Which makes the implementation of the quick principle does not apply well with the Supreme Court Circular No. 2 of 2014 in the Tangerang District Court. The rules used can not be implemented and can not be applied because they are not in accordance with the facts so that they are not in accordance with the rules and practices.